(untitled) (Bangladesh Journal of Medical Science, 2023)
Bacground: The pathogenesis of systemic mastocytosis with associated haematological neoplasm (SMAHN) is not well understood. Both diagnoses heavily rely on morphological evaluation because SM is rarely suspected in clinical practise. Objective: This case highlighted a possible delay in diagnosis due to underlying conditions or diseases. Case Report: We present a case of a patient with acute myeloid leukaemia (AML), acute myelomonocytic subtype, and concurrent mastocytosis according to World Health Organization (WHO) classification. Due to an extensive accumulation of AML blast cells that obscured the mast cell infiltrates, mastocytosis was not evident at the first diagnosis. Discussion and conclusion: The diagnosis, in this case, was established only in the third bone marrow biopsy after chemotherapy. A high index of suspicion with morphological and immunohistochemical evaluations for neoplastic mast cell populations should be considered. The optimal treatment approach should be chosen based on these two disease entities. Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 937-941